Morphology, anatomy and palynology study on Turkish endemic species Saponaria karapinarensis (Caryophyllaceae) - Ulukuş Deni̇z (Phytotaxa, 2018)
Saponaria karapinarensis (Caryophyllaceae), an endemic species from Turkey, was studied from taxonomic point of view. Morphological, anatomical, and palynological characteristics of the species were examined. Morphology of stem, calyx, petals, and capsule are useful to distinguish the species. Anatomical features, such as the number of cortex layers and sclerenchymatic cell layers in stem, are of taxonomical importance. SEM Scanning Electron Microscopy (SEM) studies on the pollen grains have revealed that they are spheroideae and their exine ornamentation is granulatae, spinulate microechinatae- microperforatae. Seed micromorphological features were also given.